2018
DOI: 10.1136/archdischild-2017-314281
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of human parechovirus infection in infants in England during 2016: epidemiology and clinical characteristics

Abstract: HPeV is an important cause of febrile illness in infants and can have severe clinical presentations. Early diagnosis may help reduce antimicrobial use, unnecessary investigations and prolonged hospitalisation. While prognosis remains favourable, some infants will develop long-term complications-paediatricians should ensure appropriate follow-up after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 23 publications
(13 reference statements)
7
35
0
2
Order By: Relevance
“…Most of these studies were conducted >20 years ago, used crude developmental assessment tools at inconsistent times after the acute illness and evaluated small numbers of infants. Notably, in our cohort, although only 189 infants underwent audiological testing after hospital discharge, none had hearing loss, which is in keeping with another recent UK national surveillance of 106 infants with HPeV and supports current consensus that audiological follow-up after hospital discharge in infants with EV and HPeV meningitis is not routinely required in infants who are otherwise well at hospital discharge 25…”
Section: Discussionsupporting
confidence: 91%
“…Most of these studies were conducted >20 years ago, used crude developmental assessment tools at inconsistent times after the acute illness and evaluated small numbers of infants. Notably, in our cohort, although only 189 infants underwent audiological testing after hospital discharge, none had hearing loss, which is in keeping with another recent UK national surveillance of 106 infants with HPeV and supports current consensus that audiological follow-up after hospital discharge in infants with EV and HPeV meningitis is not routinely required in infants who are otherwise well at hospital discharge 25…”
Section: Discussionsupporting
confidence: 91%
“…PeV infection risk increased during summer, in agreement with some [2,3,7,11,15], but not all studies as late autumn peaks are also reported [6,11,13,15]. Presence of older household siblings was not associated with PeV or PeV-A3 infections within ORChID, a finding contrasting with hospital-based studies focusing mainly on PeV-A3 cases [33,34].…”
Section: Discussionsupporting
confidence: 56%
“…PeV-A1 detections occurred earlier than PeV-A3, agreeing with seroprevalence findings [10,11], but conflicting with RT-PCR-based studies [11,31]. However, the RT-PCR studies relied upon clinical samples, which may bias the PeV detection ages as PeV-A3 is associated primarily with disease before age 3 months [2,3,5,7,11]. Unlike stools, PeV was detected rarely in nasal swabs (0.2%) and was always associated with a PeV-positive stool of the same genotype, supporting fecal-oral as one transmission route.…”
Section: Discussionmentioning
confidence: 83%
“…The age distribution, specifically the younger age preference of these viruses, as shown in this study, are possibly due to an actual age preference of the HPeVs [14,22] or selection bias due to the relatively mild symptoms in older children. Patients with low immunity are susceptible to viral infection, especially with rotaviruses; however, the presence of an intact immune system might deter the process of viral infection.…”
Section: Discussionmentioning
confidence: 60%
“…This retrospective chart review study was performed on children who underwent cerebrospinal fluid (CSF) examination in the CHA Bundang Hospital for ME diagnosis due to fever or neck stiffness symptoms from 1st June 2018 to 31st August [10,[14][15][16][17]. We enrolled 228 patients all below 15 years of age who underwent lumbar puncture.…”
Section: Patient Enrollment Study Population and Study Designmentioning
confidence: 99%